FORMULATION AND PHYSICAL QUALITY TEST OF LIP BALM AID FROM ROSELLA FLOWER EXTRACT (Hibiscus sabdariffa L.) - Cikra Ikhda Safitri; Sheila Kurniawati (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2025)
This project intends to create a new lip balm by utilizing rosella flower extract (Hibiscus sabdariffa) as a natural active ingredient and evaluating its physical quality. Rosella flowers were also chosen because they have potential benefits for lip health. Rosella flowers contain active compounds such as tannins, alkaloids, and flavonoids that function as antioxidants. The quality test of rosella flowers was carried out based on SNI standards, which included testing pH, viscosity, organolepis, homogeneity, spreadability test, and product spreadability. These findings are expected to be an innovative alternative in skin care based on local, natural and environmentally friendly ingredients. As well as increasing the understanding of plant extracts in the cosmetic industry.